A prospective study on the dimensions of global brands, brand equity and brand value - Motter Junior, Mario Divo (2016)
This doctoral thesis is about global brands under several perspectives, starting this study with and overview on the matter, followed by a 'step ahead' in the conceptualization of brand equity and brand value. As the global marketplace dynamically increases, there are theoretical and empirical challenges concerning the global brands that ask for more branding researches, trying to tune and to contextualize meanings and attributes. Thereafter, the thesis intends to provide a discussion about the industry and country-of-origin effects (and their interactions) on the brand value and the firm market value. Finally, the thesis offers an interesting comparison about the practitioners’ perspectives on the dimensions of global brands, the brand equity and the brand value, branding and marketing, including highlights on the brand internationalization process. The thesis offers a general approach on the extant literature in the first chapter, and a specific literature review for each other chapter.